2004
DOI: 10.1093/nar/gkh540
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the unwinding activity of the dimeric RECQ1 helicase in the presence of human replication protein A

Abstract: RecQ helicases are required for the maintenance of genome stability. Characterization of the substrate specificity and identification of the binding partners of the five human RecQ helicases are essential for understanding their function. In the present study, we have developed an efficient baculovirus expression system that allows us to obtain milligram quantities of recombinant RECQ1. Our gel filtration and dynamic light scattering experiments show that RECQ1 has an apparent molecular mass of 158 kDa and a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 72 publications
6
139
1
Order By: Relevance
“…Previous biochemical investigations of human RECQ1 used a full-length recombinant protein produced in insect cells. The full-length protein (RECQ1 FL ) appears as a mixture of different oligomeric forms (23,29). In common with other proteins of the RecQ family, RECQ1 FL has DNA-dependent ATPase activity, unwinds forked DNA substrates, resolves HJs, and has a DNA strand-annealing activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous biochemical investigations of human RECQ1 used a full-length recombinant protein produced in insect cells. The full-length protein (RECQ1 FL ) appears as a mixture of different oligomeric forms (23,29). In common with other proteins of the RecQ family, RECQ1 FL has DNA-dependent ATPase activity, unwinds forked DNA substrates, resolves HJs, and has a DNA strand-annealing activity.…”
Section: Resultsmentioning
confidence: 99%
“…The proteins were expressed in E. coli and purified by using nickel-affinity purification, followed by preparative gel filtration. Full-length RECQ1 was expressed in insect cells as described previously (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2, C and D); the main products of the Hel112 reaction on the HJ were Y-shaped forks, whereas only a limited amount of ssDNA was occasionally observed. Several mesophilic RecQ family helicases show the ability to unwind synthetic HJs, but in most cases, their reactions proceed up to production of ssDNA and are stimulated by ssDNA-binding proteins (37)(38)(39)(40). We reasoned that this difference might be due to spontaneous reannealing of the ssDNA products at 55°C.…”
Section: Resultsmentioning
confidence: 99%
“…Yeast Rad54 protein, Srs2 helicase, RECQ1 helicase, human Hop2-Mnd1 complex, and yeast and human RPA were purified to near homogeneity from E. coli cells tailored to express them, as described (Sigurdsson et al 2001;Krejci et al 2003;Cui et al 2004;Van Komen et al 2006;Chi et al 2007). The BLM, RECQ1, and WRN helicase preparations have been used in several of our published studies (e.g., Raynard et al 2006;Hu et al 2007) and they possess a level of DNA-dependent ATPase activity as high as or higher than that reported in the literature (Brosh et al 1999(Brosh et al , 2000Cui et al 2004; data not shown) and, as expected (Brosh et al 1999(Brosh et al , 2000Cui et al 2004), are adept at unwinding a HJ test substrate (Supplemental Fig. 6).…”
Section: Purification Of Other Proteinsmentioning
confidence: 99%